Occupational Noise Exposure in Foot and Ankle Surgery and the Risk of Noise Induced Hearing Loss - Adam Kohring DO; Joseph A.S McCahon DO; Tiffany N. Bridges DO; Stephanie Kwan DO; Selene G. Parekh MD, MBA; Joseph N. Daniel DO (Foot & Ankle Orthopaedics)
Category: Other; Basic Sciences/Biologics Introduction/Purpose: Occupational exposure to high levels of noise increases the risk of noise induced hearing loss (NIHL), resulting in significant long term quality of life implications. Hearing protection is recommended if occupational noise exposure routinely exceeds 85 dB. The purpose of this study was to determine if foot and ankle surgeons are exposed to excessive levels of noise, thus putting them at an increased risk for NIHL. Methods: A prospective review was conducted of intraoperative recordings during a variety of foot and ankle procedures. Recordings were categorized into three sub-groups: trauma, deformity correction and degenerative conditions, and soft tissue procedures. Noise levels were reported as maximum dB level (MDL), defined as the highest sound pressure level during the measurement period, and time-weighted average (TWA), defined as the average dB level projected over an 8-hour period. Dose was reported as the percentage of allowable daily noise, with projected dose reported as the measured dose projected over an 8-hours period. Results: 193 recordings consisting of 45.5% deformity correction and degenerative conditions, 27.2% soft tissue procedures, and 29.2% trauma cases. Maximal and average noise exposures were similar for all procedures (p=0.077 and p=0.090, respectively), with an average MDL of 98.9 dB and TWA of 60.5 dB. Procedures also did not significantly differ in dose (p=0.273), even when projected over an 8-hour period (p=0.362). The average MDL of TAA and arthrodesis procedures was 102.0 dB, with 52% of all deformity correction and degenerative procedures having an MDL over 100dB. Conclusion: Foot and ankle surgeons are typically not exposed to dangerous levels of occupational noise; however, specific procedures such as arthrodesis and TAA routinely achieve dangerous noise levels. Implementing protective measures is crucial for those who regularly perform these types of procedures due to the increased risk of developing NIHL.